2008
DOI: 10.1080/17470210601138746
|View full text |Cite
|
Sign up to set email alerts
|

Serial Memory for Sound-Specified Locations: Effects of Spatial Uncertainty and Motor Suppression

Abstract: According to Parmentier and Jones (2000), serial recall of locations which are specified by a sequence of sounds is prone to temporal error and is unaffected by motor suppression during retention. Studies are reported here which show that with increased spatial uncertainty at recall (Study1) and presentation (Study 2), spatial rather than temporal errors predominate. This is also the case when serial recall of sound specified locations is subject to interference from a motor suppression task (Study 3). Contrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The locality constraint also manifests in the probed recall task (Fuchs, 1969), and in the n-back task in the form of increased false alarms to n-1 and n+1 lure probes (Szmalec, Verbruggen, Kemps, & Vandierendonck, 2011). A locality constraint over the spatial-as opposed to temporal-distance between items has been witnessed in visual WM tasks (Bays, Benchmarks for Working Memory 40 2016; Emrich & Ferber, 2012;), a probed recall task (Hitch, 1974), and a reconstruction of order task for sound-specified locations (Groeger, Banks, & Simpson, 2008); the spatial transposition gradient is illustrated in the right panel of Figure 10. In sum, the locality constraint generalizes across several paradigms and materials, and has been identified as a key finding that any model of serial-order memory must predict (G. D. A.…”
Section: Benchmark 41 Confusions Of Target Item With Other Items Inmentioning
confidence: 99%
“…The locality constraint also manifests in the probed recall task (Fuchs, 1969), and in the n-back task in the form of increased false alarms to n-1 and n+1 lure probes (Szmalec, Verbruggen, Kemps, & Vandierendonck, 2011). A locality constraint over the spatial-as opposed to temporal-distance between items has been witnessed in visual WM tasks (Bays, Benchmarks for Working Memory 40 2016; Emrich & Ferber, 2012;), a probed recall task (Hitch, 1974), and a reconstruction of order task for sound-specified locations (Groeger, Banks, & Simpson, 2008); the spatial transposition gradient is illustrated in the right panel of Figure 10. In sum, the locality constraint generalizes across several paradigms and materials, and has been identified as a key finding that any model of serial-order memory must predict (G. D. A.…”
Section: Benchmark 41 Confusions Of Target Item With Other Items Inmentioning
confidence: 99%
“…Although most studies of spatial short-term memory for order have employed visual–spatial stimuli, a few studies have used auditory–spatial stimuli consisting of sequences of heard spatial locations (e.g., Groeger, Banks, & Simpson, 2008; Parmentier & Jones, 2000; Tremblay et al, 2006). In this test, a series of bursts of white noise are emitted from a number of speakers arranged in azimuth space ahead of the participant.…”
Section: Assessing Memory For Serial Ordermentioning
confidence: 99%
“…The forward serial position curves associated with the recall of sequences composed of various different types of nonverbal stimuli have been shown to exhibit an extensive primacy effect accompanied by a one-item recency effect. These stimuli include visual–spatial locations (Avons, 2007; Farrand et al, 2001; GuĂ©rard & Tremblay, 2008; Jones et al, 1995; Smyth & Scholey, 1996; Tremblay et al, 2006), visual–spatial movements (Agam et al, 2005, 2007, 2010), auditory–spatial locations (Groeger et al, 2008; Parmentier & Jones, 2000; Tremblay et al, 2006), visual matrix patterns (Avons, 1998; Avons & Mason, 1999), and unfamiliar faces (Smyth et al, 2005; G. Ward et al, 2005).…”
Section: Major Phenomena Of Memory For Serial Ordermentioning
confidence: 99%
“…A large volume of psychological experiments has demonstrated that the retrieval performances of human subjects are associated with the order of presented items, displaying a serial position effect, namely, subjects exhibit better performances for memory items appearing at the beginning or at end of a sequence, called the primacy or recency effect, respectively (Simon, 1962 ; Postman and Phillips, 1965 ; Glanzer and Cunitz, 1966 ). This serial position effect is observed in various types of working memory systems, including visual (Kiani et al, 2008 ), auditory (Hurlstone et al, 2014 ; Borderie et al, 2024 ), and spatial working memories (Groeger et al, 2008 ). The serial position effect is a well-established phenomenon in memory research, yet its underlying neural mechanism, contextual variation, and functional implication remain largely unresolved.…”
Section: Introductionmentioning
confidence: 98%